Nutritional Modulation of Immune Function: Analysis of Evidence, Mechanisms, and Clinical Relevance - Wu, Dayong; Lewis, Erin D.; Pae, Munyong; Meydani, Simin Nikbin (Frontiers in Immunology, 2019)
It is well established that the nutritional deficiency or inadequacy can impair immune functions. Growing evidence suggests that for certain nutrients increased intake above currently recommended levels may help optimize immune functions including improving defense function and thus resistance to infection, while maintaining tolerance. This review will examine the data representing the research on prominent intervention agents n-3 polyunsaturated fatty acids (PUFA), micronutrients (zinc, vitamins D and E), and functional foods including probiotics and tea components for their immunological effects, working mechanisms, and clinical relevance. Many of these nutritive and non-nutritive food components are related in their functions to maintain or improve immune function including inhibition of pro-inflammatory mediators, promotion of anti-inflammatory functions, modulation of cell-mediated immunity, alteration of antigen-presenting cell functions, and communication between the innate and adaptive immune systems. Both animal and human studies present promising findings suggesting a clinical benefit of vitamin D, n-3 PUFA, and green tea catechin EGCG in autoimmune and inflammatory disorders, and vitamin D, vitamin E, zinc, and probiotics in reduction of infection. However, many studies report divergent and discrepant results/conclusions due to various factors. Chief among them, and thus call for attention, includes more standardized trial designs, better characterized populations, greater consideration for the intervention doses used, and more meaningful outcome measurements chosen.